Lack of eye discipline during headers in high school girls soccer: A possible mechanism for increased concussion rates. (March 2017) - Clark, Joseph F.; Elgendy-Peerman, Hagar T.; Divine, Jon G.; Mangine, Robert E.; Hasselfeld, Kimberly A.; Khoury, Jane C.; Colosimo, Angelo J.
Abstract: The sport of soccer is the fastest growing and most popular sport worldwide. With this growth and popularity, attention needs to be given to this athletic population. Sports related concussions is a topic that has gained attention both in the media and by governmental organizations, with growing initiatives in diagnosis, prevention and treatment. The act of soccer heading is thought to contribute to increased concussion incidence. Current evidence reveals that within the high school soccer athletic population, female athletes incur a higher concussion rate than males. This is often attributed to many things including differing cervical spinal musculature, skull thickness, etc., but a definitive reason has not yet been found. Other behaviors, such as field awareness and eye discipline™ on the field of play, may also be contributing factors that result in females incurring a greater concussion rate than males. For the purposes of this paper we define eye discipline™ as the ability to keep the eyes engaged in sporting activity with high risk potential. We present our hypothesis that high school female soccer players are more likely to have their eyes closed when in position for heading the ball as compared to high school male soccer players and this lack of visual awareness may increase the risk of concussion. Should these differences be substantiated between males and females, it may initiate and promote discussion of the need for vision training in the high school athletic setting. As a tool for injury prevention, vision training may improve specific visual parameters improving athletes' abilities to process the field of play and prepare for or avoid injury causing situations. Through ocular motor and visual conditioning, an athlete may become more eye disciplined™, and more likely to have their eyes open during heading of the ball, and more likely to avoid concussions.